An Adsorptive and Antioxidant Vaginal Gel Clears High-Risk HPV- and p16/Ki-67-Associated Abnormal Cytological Cervical Findings: A post-hoc Subgroup Analysis of a Prospective Randomized Controlled Trial on CIN2 and p16 Positive CIN1 - Major, Attila Louis; Skřivánek, Ales; Grandjean, Etienne Marc; Dvořák, Vladimír; Malík, Tomáš; Pluta, Marek; Mayboroda, Ivanna (Frontiers in Medicine, 2021)
Objective: To analyze the course of p16/Ki-67-positive abnormal cytological cervical findings and hr-HPV- and p16/Ki-67-clearances in women treated with a vaginal gel. Methods: 172 women with a histological diagnosis of CIN2 or p16-positive CIN1 lesions were selected based on a positive cytological p16/Ki-67 test. For three months 75 patients in the active arm (AA) daily applied 5 ml of a vaginal gel. 97 patients in the control arm (CA) underwent no treatment (“watchful waiting”). Endpoints were cytological evolution, p16/Ki-67- and hr-HPV-clearances. Results: At 3 months cytological regression was observed in 76% (57/75) of patients in the AA compared with 24.7% (24/97) in the CA. Progression occurred in 5.3% (4/75) of the AA compared with 15.5% (15/97) of the CA. The p16/Ki-67 status change was significantly (p<0.001) in favor of the AA: 77.3% (58/75) became negative compared to 20.6% (20/97) in the CA. hr-HPV prevalence decreased significantly (p<0.001) in the AA from 86.7% to 44.0%, while increasing in the CA from 78.4% to 83.5%. Cytological regression and p16/Ki-67 changes remained in the AA at six months. Conclusions: The vaginal gel significantly cleared hr-HPV and p16/Ki-67 and treatment was associated with improved cytological findings, thereby offering an effective option against oncogenic risk. Trial registration number: ISRCTN11009040, date of registration: 10/12/2019